THE EFFECT OF REMOTE WORK ON EMPLOYEE PERFORMANCE FOR COMPANIES IN GREATER JAKARTA AREA - Makarim, Abiseno Aryo; Pratama, Andika Putra (International Journal of Social Service and Research, 2024)
Remote work has emerged as a significant trend that redefines traditional work arrangements. This study aims to investigate whether these concerns are justified by actual productivity differences or if they stem from a placebo effect, ultimately seeking evidence-based insights to inform workplace practices and evaluate the impact of remote work on employee productivity in the Greater Jakarta Area. The study employed a qualitative design with a case study approach to explore employee perceptions, attitudes, and experiences regarding remote work, focusing on how different types of tasks perform in remote versus in-office settings. The analysis aimed to highlight factors that influence productivity in a work-from-home (WFH) context, enhancing the understanding of employee performance variability. The findings reveal that task types significantly affect productivity in remote work settings. Based on the findings, several practical recommendations are proposed for companies, including JAR, to enhance their remote work environments: enhanced communication tools, clear work-life boundaries, robust organizational support systems, and opportunities for social interaction.